A Patient with Platelet Transfusion Refractoriness - Wint Wint Thu Nyunt; Rabeya Yousuf; S Fadilah S Abdul Wahid, (Malaysian Journal of Science (MJS), 2025)
Platelet transfusion refractoriness is a less-than-expected increase in platelet count following platelet transfusions. We report a case of platelet transfusion refractoriness with identification of anti-HLA class I alloantibody. In patients with thrombocytopenia, even when multiple established aetiologies are present, it is essential to recognise platelet transfusion refractoriness and to perform further laboratory investigations, including platelet immunology test. This approach enables identification of additional contributing factors to thrombocytopenia and clarification of the underlying causes of platelet refractoriness, thereby guiding appropriate therapeutic strategies.